Discriminant musculo-skeletal leg characteristics between sprint and endurance elite Caucasian runners - Bex, T.; Iannaccone, F.; Stautemas, J.; Baguet, A.; De Beule, M.; Verhegghe, B.; Aerts, P.; De Clercq, D.; Derave, E. (Scandinavian Journal of Medicine & Science in Sports, 2017)
Excellence in either sprinting or endurance running requires specific musculo-skeletal characteristics of the legs. This study aims to investigate the morphology of the leg of sprinters and endurance runners of Caucasian ethnicity. Eight male sprinters and 11 male endurance runners volunteered to participate in this cross-sectional study. They underwent magnetic resonance imaging and after data collection, digital reconstruction was done to calculate muscle volumes and bone lengths. Sprinters have a higher total upper leg volume compared to endurance runners (7340 vs 6265 cm3). Specifically, the rectus femoris, vastus lateralis, and hamstrings showed significantly higher muscle volumes in the sprint group. For the lower leg, only a higher muscle volume was found in the gastrocnemius lateralis for the sprinters. No differences were found in muscle volume distribution, center of mass in the different muscles, or relative bone lengths. There was a significant positive correlation between ratio hamstrings/quadriceps volume and best running performance in the sprint group. Sprinters and endurance runners of Caucasian ethnicity showed the greatest distinctions in muscle volumes, rather than in muscle distributions or skeletal measures. Sprinters show higher volumes in mainly the proximal and lateral leg muscles than endurance runners.